METTL3 inhibition promotes radiosensitivity in hepatocellular carcinoma through regulation of SLC7A11 expression - Chen Zhang; Tianpeng Yang; Hanbin Chen; Xiaofeng Ding; Huajian Chen; Zhenzhen Liang; Yinlong Zhao; Shumei Ma; Xiaodong Liu (Cell Death and Disease, 2025)
Abstract Radiotherapy is one of the main treatment modalities for advanced hepatocellular carcinoma (HCC). Ferroptosis has been shown to promote the radiosensitivity of HCC cells, but it remains unclear whether epigenetic regulations function in this process. In this study, we found that the overexpression of METTL3 was associated with poor prognosis. Knockdown of METTL3 promoted radiosensitivity of HCC by inducing ferroptosis. Mechanistically, METTL3 targeted adenine (+1795) on the SLC7A11 mRNA, and the m6A reader IGF2BP2 promoted SLC7A11 mRNA stability by recognizing and binding to the m6A site. Additionally, METTL3 decreased the ubiquitination of SLC7A11 protein through the m6A/YTHDF2/SOCS2 axis. Furthermore, in vivo studies showed that HCC models with low METTL3/IGF2BP2 expression have higher radiosensitivity. In conclusion, our study suggests that METTL3 regulates the stability of SLC7A11 mRNA in an m6A/IGF2BP2-dependent manner and the ubiquitination of SLC7A11 protein through the m6A/YTHDF2/SOCS2 pathway, both of which require the m6A methyltransferase activity of METTL3. METTL3 or IGF2BP2 may be promising targets for radiotherapy of HCC.